The Influence of Facilities and Infrastructure Management, Principal Communication, and Work Motivation on the Performance of Junior High School Teachers in Maro Sebo Ulu District, Batang Hari Regency - Trijayanti, Yuni; K.A Rahman, K.A Rahman; Habibi, Akhmad (Journal Development Manecos, 2026)
This study examines the influence of facilities and infrastructure management, principal communication, and work motivation on teacher performance in public junior high schools in Maro Sebo Ulu District, Batang Hari Regency, Indonesia. Teacher performance has become a critical concern in educational management because it directly affects instructional quality and the achievement of educational objectives. Employing a quantitative explanatory research design, this study involved all 132 teachers in the district using a total sampling technique. Data were collected through a structured questionnaire measured on a five-point Likert scale and analyzed using descriptive statistics and multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, validity, reliability, normality, multicollinearity, and linearity tests were conducted to ensure the quality of the data and the suitability of the regression model. The findings reveal that facilities and infrastructure management, principal communication, and work motivation each have a positive and significant effect on teacher performance. Principal communication emerged as the strongest predictor of teacher performance and demonstrated a substantial influence on teacher work motivation. Facilities and infrastructure management contributed positively to both teacher motivation and performance, although its effect was comparatively smaller. Furthermore, work motivation significantly enhanced teacher performance, indicating its role as an important psychological mechanism linking organizational support and professional effectiveness. Simultaneously, the three independent variables explained 36.0% of the variance in teacher performance. The study concludes that improving teacher performance requires an integrated management approach that combines effective leadership communication, supportive resource management, and sustained efforts to strengthen teacher motivation. These findings contribute to educational management literature by highlighting the strategic role of leadership communication in fostering teacher effectiveness and organizational performance.